IMPLEMENTING AN INTERNAL CONTROL STRATEGY FOR THE PERFORMANCE OF PUBLIC SECTOR ORGANIZATIONS - Vanya Nurul Izza; Nuri Aslami (International Journal Labs, 2022)
Strategic management is not only applied to the private sector but has also been applied to the public sector. The implementation of strategic management in the two sectors is actually not that much different, it's just that public sector institutions do not emphasize the organization's goal to seek profit but rather to serve the community. The stages of strategic management begin with strategy formulation, strategy implementation and strategy evaluation. The implementation of public sector strategic management is one of the best ways to achieve good governance. In an effort to realize a better performance of government organizations in providing services to the community, the implementation of strategic management for public sector organizations is very important to improve the effectiveness of the performance of public sector organizations. This requires public sector organizations to think strategically, be able to translate their inputs into effective strategies, and develop the rationale needed to lay the foundation for implementing their strategies. Implementation of strategic management in public sector organizations is expected to assist the organization in realizing its vision and mission. Although the outcome orientation to be achieved by implementing strategic management between the private sector and the public sector is slightly different, the two sectors certainly face different environmental conditions which become their own obstacles in the process of implementing strategic management. To overcome the obstacles that occur, one of them is by using a SWOT analysis approach (strength, weakness, opportunity, and threats). -constraints that occur in measuring the performance of public sector organizations